Evaluating the Success of the War on Poverty since 1963 Using an Absolute Full-Income Poverty Measure - Burkhauser, Richard V.; Corinth, Kevin; Elwell, James; Larrimore, Jeff (Journal of Political Economy, 2024)
We evaluate progress in the War on Poverty as President Lyndon B. Johnson defined it, which established a 20% baseline poverty rate and adopted an absolute standard. While the official poverty rate fell from 19.5% in 1963 to 10.5% in 2019, our absolute full-income poverty measure—which uses a fuller income measure and updates thresholds only for inflation—fell from 19.5% to 1.6%. However, we also show that relative poverty reductions have been modest. Additionally, government dependence increased over this time, with the share of working-age adults receiving under half their income from market sources more than doubling.